Are older people prescribed antidepressants on the basis of fewer symptoms of depression, and for longer periods of time? A survey of 1825 New Zealanders. (11th March 2016) - Read, John; Gibson, Kerry L; Cartwright, Claire
Abstract : Aim: To determine whether older people are prescribed antidepressants at lower levels of depression and with fewer symptoms, and whether they are more likely to engage in chronic usage than younger adults. Methods: An online survey about experiences with, and opinions about, depression and antidepressants was completed by 1825 New Zealand adults who had been prescribed antidepressants in the preceding five years. Results: Participants over 55 were prescribed antidepressants with significantly fewer symptoms and were significantly less likely to meet DSM criteria for depression. They were also significantly more likely to have used the drugs for three years and still be using them. Conclusion: Prescribing physicians and their older patients might benefit from discussing the pros and cons of antidepressants (including the additional risk factors with this age group) and the alternatives. If prescription does occur, careful monitoring to avoid unnecessary, potentially damaging, long‐term use is recommended.